The preferences and practices regarding refractive surgeries among Saudi Ophthalmology Society members - Abdullhamid S AlGhamdi; Rahma A AlGethami; Nada Ahmad Almalki; Abdulrahman Mohammed Al-Amri; Ma'an Al-Barry (Saudi Journal for Health Sciences, 2022)
Background: Refractive errors are the leading cause of visual impairments in the Kingdom of Saudi Arabia (KSA). Laser refractive eye surgeries are getting huge popularity for correcting these visual impairments in KSA and other gulf countries. Aims: The study assessed the preferences and practices regarding refractive surgeries The preferences and practices regarding refractive surgeries among Saudi ophthalmology society members. Setting and Design: A cross-sectional study was conducted using an online questionnaire among the Saudi Ophthalmology Society members. Methods and Materials: The questionnaire was pilot tested and had 28 items that included sociodemographic details and practices related to refractive eye surgery of participating ophthalmologists. Statistical Analysis: The collected data was analyzed using Pearson's Chi-square test to determine the relationship between categorical variables. Results: Excimer laser platform EX500 (Alcon) was the most commonly used refractive surgery system. There were region-wise differences observed in the type of refractive surgery system where surgeons from Central KSA used AMARIS 1050 RS (SCHWIND) (83.4%) and AMARIS 500 (SCHWIND) (68.4%) comparatively more than other regions (P < 0.05). The majority of the eye surgeons (84.4%) used Pentacam comprehensive eye scanner preoperative screening, and corneal topography was the most commonly used preoperative examination method. Only 9.1% of the surgeons had refractive eye surgery on 75%–100% of their patients, and the most commonly preferred refractive eye surgery (RES) by the surgeons in our study was photorefractive keratectomy. Conclusion: The findings showed that refractive eye surgery trends are changing, and surgeons are shifting to more reliable techniques with fewer postsurgical complications.